Determination of functional ABCG2 activity and assessment of drug–ABCG2 interactions in dairy animals using a novel MDCKII in vitro model. Issue 2 (28th November 2012) - Wassermann, Louise; Halwachs, Sandra; Lindner, Stefan; Honscha, Kerstin U.; Honscha, Walther
Abstract The ATP‐binding cassette subfamily G member 2 (ABCG2) transporter is a member of the ATP‐binding cassette (ABC) family of efflux carriers that mediates cellular extrusion of various drugs and toxins. In the mammary gland, ABCG2 is expressed at the apical membrane of alveolar epithelial cells and is induced during lactation. It is well established that ABCG2 plays the main role in active secretion of xenobiotics into milk of humans and mice. In contrast, no detailed information is as yet available about functional activity and substrate spectrum of ABCG2 in dairy animals. Therefore, we cloned full‐length ABCG2 from bovine, ovine and caprine lactating mammary gland tissues using rapid amplification of complementary DNA (cDNA) ends polymerase chain reaction. The generated full‐length ABCG2 cDNA constructs were stably transduced in MDCKII cells. Functional ABCG2 efflux activity was demonstrated with the Hoechst H33342 accumulation assay using the specific ABCG2 inhibitor Ko143. The established ruminant MDCKII‐ABCG2 cell culture models in conjunction with the H33342 transport assay showed interaction of various drugs such as cefalexin and albendazole with bABCG2, oABCG2 or cABCG2. Moreover, the flavonoids equol and quercetin exhibited interaction with all ruminant ABCG2 clones. Altogether, our generated cell culture models allowed rapid and high‐throughput screening of potential ruminant ABCG2 substrates and thus increase the understanding of carrier‐associated secretion of xenobiotics into milk. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:772–784, 2013